Pertuzumab retreatment for HER2‐positive advanced breast cancer: A randomized, open‐label phase III study (PRECIOUS). Issue 9 (23rd July 2022) - Yamamoto, Yutaka; Iwata, Hiroji; Taira, Naruto; Masuda, Norikazu; Takahashi, Masato; Yoshinami, Tetsuhiro; Ueno, Takayuki; Toyama, Tatsuya; Yamanaka, Takashi; Takano, Toshimi; Kashiwaba, Masahiro; Tsugawa, Koichiro; et al.
Abstract: No standard options existed for human epidermal growth factor receptor 2 (HER2)‐positive advanced breast cancer that progresses after second‐line trastuzumab emtansine therapy before 2020. The purpose of this study was to examine the efficacy of pertuzumab retreatment after disease progression following pertuzumab‐containing therapy for HER2‐positive locally advanced or metastatic breast cancer for the first time. This randomized, open‐label, multicenter phase III trial was undertaken in 93 sites in Japan. Eligible patients with HER2‐positive breast cancer who had received pertuzumab, trastuzumab, and chemotherapy as first‐ and/or second‐line therapy were randomly assigned (1:1) to: (i) pertuzumab, trastuzumab, and physician's choice chemotherapy (PTC), or (ii) trastuzumab and physician's choice chemotherapy (TC). The primary end‐point was investigator‐assessed progression‐free survival (PFS). Between August 1, 2015 and December 31, 2018, 219 patients were randomized to PTC ( n  = 110) or TC ( n  = 109). Median follow‐up was 14.2 months (interquartile range, 9.0–22.2), and median PFS was 5.3 months (95% confidence interval [CI], 4.0–6.6) with PTC and 4.2 months (95% CI, 3.2–4.8) with TC (stratified hazard ratio 0.76 [95% CI upper limit 0.967]; p  = 0.022). Progression‐free survival was improved by adding pertuzumab in all prespecified subgroups. The PTC arm showed a trend towards better overall survival and duration of response, but similar objective response and health‐related quality of life. The incidence of treatment‐related adverse events was similar between groups except for diarrhea. Pertuzumab retreatment contributes to disease control for HER2‐positive locally advanced or metastatic breast cancer previously treated with pertuzumab‐containing regimens. Abstract : This randomized, open‐label, multicentre phase 3 trial examined the efficacy of pertuzumab retreatment after disease progression following pertuzumab‐containing therapy for HER2‐positive locally advanced or metastatic breast cancer for the first time. Patients randomly assigned to pertuzumab, trastuzumab and physician #x2019;s choice chemotherapy had improved progression‐free survival compared with those who received trastuzumab and physician #x2019;s choice chemotherapy (5.3 vs 4.2 months; p=0.022). Pertuzumab retreatment also showed a trend towards better overall survival and duration of response, and contributes to disease control for HER2‐positive locally advanced or metastatic breast cancer previously treated with pertuzumab‐containing regimens.